KONSEP KEPEMIMPINAN DALAM PERSPEKTIF ISLAM: Studi Kepemimpinan Nabi Muhammad SAW - Sumarno, Sumarno; Gesang Saputra, Alan Luthfi (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2022)
The leadership of the Prophet Muhammad in the concept of Islamic leadership came to bring a perfect government system from the past until now. In this case it shows us the perfection of Islam and its relevance in every time and place. The purpose of this study was to determine the concept of Islamic leadership carried out by the Prophet Muhammad. The qualitative research method is the object of the reference library. References or library sources related to relevant matters in this research. To obtain research data, the author uses a literature study by taking various references, both books, articles and journals that are in accordance with the urgency of leadership in an Islamic perspective. The results of this study are; 1). Islamic leadership is in accordance with the times from the past until now. 2). Prophet Muhammad as a figure and role model for today's leaders because of the leadership in the current era. 3). The leadership of the Prophet prioritized the principles of fairness, wisdom, and honesty. Keywords; Leadership, Islam, Prophet Muhammad